1975
DOI: 10.1139/b75-276
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons among isolates of Gremmeniella abietina by means of growth rate, conidia measurement, and immunogenic reaction

Abstract: Growth records among a worldwide collection of isolates of Gremmeniella abietina revealed wide variation in response at different temperatures. Overall, the fungus was identified as a facultative psychrophile with extended capacity for growth at low temperatures and a thermal-death or growth-suppression point between 25 and 30 °C. The gross appearance of cultures, extent of spore septation, and appearance of heavily sporulating and pionnotal variants provide evidence to support a concept of separate North Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 7 publications
3
36
0
Order By: Relevance
“…On the basis of immunological, biochemical and DNA profiles, G. abietina has been divided into North American, Asian and European races (Dorworth and Krywienczyk 1975, Lecours et al 1994, Hamelin et al 1993, Müller and Uotila 1997. Within the European race, three separate biotypes have been recognized: one affecting large trees (LTT), one affecting small trees (STT) and an alpine type (Hellgren and Högberg 1995, Hamelin et al 1996, Petäistö et al 1996.…”
Section: Scleroderris Cankermentioning
confidence: 99%
“…On the basis of immunological, biochemical and DNA profiles, G. abietina has been divided into North American, Asian and European races (Dorworth and Krywienczyk 1975, Lecours et al 1994, Hamelin et al 1993, Müller and Uotila 1997. Within the European race, three separate biotypes have been recognized: one affecting large trees (LTT), one affecting small trees (STT) and an alpine type (Hellgren and Högberg 1995, Hamelin et al 1996, Petäistö et al 1996.…”
Section: Scleroderris Cankermentioning
confidence: 99%
“…Morelet, the causal agent of Scleroderris canker of conifers, is a damaging fungal pathogen in the pine plantations and tree nurseries in North America, Europe and Asia (Gibbs 1984;Laflamme 1993;Laflamme and Lachance 1987;Setliff et al 1975;Skilling et al 1986;Yokota et al 1974). Dorworth and Krywienczyk (1975) recognized three races of G. abietina based on serological tests. Thèse three races (North American (NA), European (EU) and Asian) are confined to the abietina variety of this species (Petrini étal.…”
Section: Introductionmentioning
confidence: 99%
“…Marosy et al (1989) found that disease symptoms developed in seedlings either after 44 days, when the temperature remained between −6°C and 5°C, or when the plants were covered by snow. Although G. abietina grows more rapidly as temperature increases up to about 18°C (Sletten 1971), it has been found to grow at temperatures as low as zero or even under subzero conditions (Ettlinger 1945, Sletten 1971, Yokota et al 1974, Dorworth & Krywienczyk 1975, Marosy et al 1989). Petäistö (1993) has shown that fungus caused necrosis in seedlings during winter even at −4°C, when mycelia had been set beneath the phloem.…”
Section: Introductionmentioning
confidence: 99%